In the secret of a revolutionary laboratory (Prassi Ecdotiche della Modernità Letteraria, 2024)
The paper offers a meticulous overview of the guiding principles and decisions that have shaped the preparation of the National Edition of Giovanni Verga’s Works: the progress achieved to date, the ongoing efforts, and the plans for the future, both immediate and long-term. Retracing the stages involved in the creation of such a monumental undertaking as the National Edition of Verga’s works inevitably means, in the author’s own words, «charting the history [...] of authorial philology as applied to prose texts in the late 20th century». From the earliest editions of Verga’s works to the establishment of the Verga Foundation, from the inception of the first series of the National Edition to the critical exploration of Verga’s correspondence, this account provides a detailed map of the genesis and development of the literary production and critical study of a pillar of Italy’s narrative tradition.